2021
DOI: 10.1021/acs.jpclett.0c03401
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Approach to Screen Semiconducting MOFs Using Bloch Mode Analysis and Spectroscopic Measurements

Abstract: A rapid and simple analytical approach is developed to screen the semiconducting properties of metal organic frameworks (MOFs) by modeling the band structure and predicting the density of state of isoreticular MOFs (IRMOFs). One can consider the periodic arrangement of metal nodes linked by organic subunits as a 1D periodic array crystal model, which can be aligned with any unit-cell axis included in the IRMOF's primitive cubic lattice. In such a structure, each valence electron of a metal atom feels the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
8
5
0
Order By: Relevance
“…We note that if one neglects the lowest energy peak in the UV-Vis absorption spectra reported by the early study by Tachikawa et al 18 which was later attributed to the ZnO impurity (at 3.6 eV), the agreement with our results is excellent. In their work, the most intense band is located at ∼5.2 eV (240 nm) and the next one with much lower intensity is found at 4.3 eV (290 nm), in agreement with our study and with the recent experimental reports by Rathnayake et al 43…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We note that if one neglects the lowest energy peak in the UV-Vis absorption spectra reported by the early study by Tachikawa et al 18 which was later attributed to the ZnO impurity (at 3.6 eV), the agreement with our results is excellent. In their work, the most intense band is located at ∼5.2 eV (240 nm) and the next one with much lower intensity is found at 4.3 eV (290 nm), in agreement with our study and with the recent experimental reports by Rathnayake et al 43…”
Section: Resultssupporting
confidence: 93%
“…The BSE yields an optical gap of 4.5 eV with an intense absorption peak at 5.3 eV in good agreement with experimental studies. 24,43 The optical absorption is dominated by ligand-centered transitions at least up to ∼ 6 eV, also in agreement with inferences drawn in recent experimental studies. 16,20 The large dierence between the fundamental gap and optical band gap points to strongly bound excitons in the studied spectral region with binding energies of several eVs, previously not discussed in literature.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We note that if one neglects the lowest energy peak in the UV-Vis absorption spectra reported by the early study by Tachikawa et al 18 which was later attributed to the ZnO impurity (at 3.6 eV), the agreement with our results is excellent. In their work, the most intense band is located at ∼5.2 eV (240 nm) and the next one with much lower intensity is found at 4.3 eV (290 nm), in agreement with our study and with the recent experimental reports by Rathnayake et al 43…”
Section: Resultssupporting
confidence: 93%
“…Direct and inverse photoemission spectroscopy should be employed to this purpose and we are condent that experiments of this kind will conrm our results. Absorption (a.u) Optical absorption spectrum of MOF-5 computed using BSE/evGW /Gau-PBE (upper panel) and measured (lower panel) by Rathnayake et al 43 Hole and electron densities of the excitons reported as colored dots in the spectrum (lower gure).…”
Section: Discussionmentioning
confidence: 99%